Teaching Cases on Entrepreneurship and Innovation: Unexplored Topics and Contexts - Samantha Burvill (Edward Elgar Publishing Limited, 2024)
Cases on Entrepreneurship and Innovation bridges the gap between the real-world complexities of diverse innovative and entrepreneurial endeavours in challenging environments and the academic classroom setting. It serves as an essential toolkit for academics and instructors, providing clear teaching guidance and tailoring real-world scenarios to be more relatable and context-relevant for students across the globe.